CAFF Technical Report No. 21 - ARCTIC BIRDS INTERNATIONAL BREEDING CONDITIONS SURVEY BULLETIN No. 11 - Soloviev, M.Y. Ed.; Tomkovich, P.S. Ed. (CAFF International Secretariat, 2010)
CAFF Technical Report No. 21 - ARCTIC BIRDS INTERNATIONAL BREEDING CONDITIONS SURVEY BULLETIN No. 11